The Role of Erythropoietin in Metabolic Regulation - Weiqin Yin; Constance T. Noguchi (Cells, 2025)
Erythropoietin (EPO) is a key regulator of erythrocyte production, promoting erythroid progenitor cell survival, division, and differentiation in the fetal liver and adult bone marrow. Mice lacking EPO or its receptor (EPOR) die in utero due to severe anemia. Beyond hematopoiesis, EPO influences non-hematopoietic tissues, including glucose and fat metabolism in adipose tissue, skeletal muscle, and the liver. EPO is used to treat anemia associated with chronic kidney disease clinically and plays a role in maintaining metabolic homeostasis and regulating fat mass. EPO enhances lipolysis while inhibiting lipogenic gene expression in white adipose tissue, brown adipose tissue, skeletal muscle, and the liver, acting through the EPO-EPOR-RUNX1 axis. The non-erythroid EPOR agonist ARA290 also improves diet-induced obesity and glucose tolerance providing evidence for EPO regulation of fat metabolism independent of EPO stimulated erythropoiesis. Therefore, in addition to the primary role of EPO to stimulate erythropoiesis, EPO contributes significantly to EPOR-dependent whole-body metabolic response.